2015
DOI: 10.1007/s12072-015-9645-x
|View full text |Cite
|
Sign up to set email alerts
|

Aligning to the sample-specific reference sequence to optimize the accuracy of next-generation sequencing analysis for hepatitis B virus

Abstract: BackgroundHepatitis B virus (HBV) quasispecies are crucial in the pathogenesis of chronic liver disease. Next-generation sequencing (NGS) is powerful for identifying viral quasispecies. To improve mapping quality and single nucleotide variant (SNV) calling accuracy in the NGS analysis of HBV, we compared different mapping references, including the sample-specific reference sequence, same genotype sequences and different genotype sequences, according to the sample.MethodsReal Illumina HBV datasets from 86 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Moreover, different reference sequences also might mean different performances on mapping. Liu et al found when the sample-speci c sequence, a sequence with the same genotype sequence as the sample, was used as the mapping reference in NGS analyses of HBV(Hepatitis B Virus), the mapping accuracy and variation calling were optimized, compared to when the other four commonly used HBV genome sequences from GenBank database were respectively used as the mapping references [15].The present study provides an important recommendation for the selection of reference sequences for homology analysis. We compared three references ( the mitogenome alignment showed the brilliant performance than the other two references.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, different reference sequences also might mean different performances on mapping. Liu et al found when the sample-speci c sequence, a sequence with the same genotype sequence as the sample, was used as the mapping reference in NGS analyses of HBV(Hepatitis B Virus), the mapping accuracy and variation calling were optimized, compared to when the other four commonly used HBV genome sequences from GenBank database were respectively used as the mapping references [15].The present study provides an important recommendation for the selection of reference sequences for homology analysis. We compared three references ( the mitogenome alignment showed the brilliant performance than the other two references.…”
Section: Discussionmentioning
confidence: 89%
“…Optimized highly similar sequences have always been an important selection of reference sequences during the homologous sequences alignment to assist in piecing reads together. In order to accurately construct a genome sequence from NGS data, many studies turn to exploring the optimal sequencing methods and alignment strategies [14][15][16][17][18][19][20]. The de novo and reference-based approaches were used to assemble the complete mitogenome of Clarias batrachus from NGS data, respectively, which resulted in different consensus sequences in length [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGS or ultra-deep sequencing generates large volumes of data, which can only be analyzed using bioinformatics tools and provides large coverage that can detect minor quasispecies populations of HBV [46][47][48][49][50][51] that may be important in understanding HBV pathogenicity and response to treatment. In order to minimize the number of artifactual calls of single-nucleotide variations in NGS, it is important that the correct reference sequences are used [51,52].…”
Section: Evolutionmentioning
confidence: 99%
“…A sample-specific reference sequence is the consensus sequence obtained from the NGS reads of each sample through alignment with its same genotype mapping reference. In our demonstrations, we found that using this type of reference sequence as the mapping reference has the best mapping quality and the highest single nucleotide variant (SNV) calling accuracy, as compared with using the compatible genotype sequence [ 66 ]. The percentage of false SNV calls increased significantly from 0.09% using a sample-specific reference sequence to 28.95% using an incompatible genotype reference (Fig.…”
Section: Introductionmentioning
confidence: 99%